Study Of GAP Acceptance For Yield-Controlled Left-Turning Lane At Signalised Intersections - Marzuki, Noradila (Universiti Sains Malaysia, 2017)
Gap acceptance is a process where a vehicle accepts an available gap to manoeuvre in to the major traffic stream. A driver entering in to a major traffic stream must evaluate the space between potentially conflicting vehicles and have to decide whether to enter the lanes or not using the space available. Lack of adequate past study on gap acceptance for yield controlled left-turning lanes at signalised intersections in Malaysia has provided motivation for the research study. Main study of this research is to study the critical gap and follow up time at the yield controlled left-turning lanes at signalised intersection and to observe the significance of the effect of the critical gap on the queue length and delay time. Raff’s method is used to estimate the critical gap at the intersection. Raff’s method is frequently used because of its simplicity and also been used in the study. Raff’s method used gaps offered to the drivers which is the time between the arrivals of minor stream vehicle at a give-way line to the arrival of the next vehicle in the major stream. Each driver is offered one gap and they can then decide to accept or reject the gap. The critical gap is assumed to have the same value as critical lag. The value of critical gap obtained for motorcycles that used the yield controlled left-turning lanes at signalised intersection is 1.25 seconds. The value of critical gap obtained for left-turn lane with deceleration lane is 1.25 seconds and without deceleration lane is 1.20 seconds.